Numerical simulation of aerosol particle aspiration in a passive sampler. Issue 6 (August 2019) - Soloveva, O V; Solovev, S A; Sh Misbakhov, R
Abstract: A mathematical model and numerical calculations of the coefficient of aerosol aspiration into a passive sampler are realized. In the absence of the effect of particles influence on the gas flow the carrier medium is calculated in the approximation of an incompressible potential flow by the boundary element method. The equations of motion of the particles are calculated in the velocity field results to determine the coefficient of aspiration. The coefficient of the aspiration depending on the Stokes number and sampler angle is studied.